TEACHERPRENEURSHIP KREATIF : STUDI KASUS KEWIRAUSAHAAN MELALUI STUP ROTI - Chandra Widya Kesumadyaningtyas; Hanifatul Fadilah; Naila Rosida; Nia Ansyafani (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2025)
This discussion was conducted to determine the implementation of teacher entrepreneurship in an elementary school teacher who manages a side business selling bread stup with a monthly ordering scheme, and to analyze how this activity remains consistent with the spirit of professionalism of an educator. Using a descriptive qualitative research approach, the investigation was conducted at SDIT Mutiara Umat with detailed interviews, observations, and analysis to ensure the validity of the findings. Data analysis concluded that the teacher successfully maintained his professional dedication, which was reflected in punctuality in attendance, careful pedagogical planning, and a clear differentiation between teaching duties and entrepreneurial activities. Side business activities offer benefits in the form of improved financial conditions, increased entrepreneurial skills, and serve as role models for students in developing independence and creativity. However, the implementation of teacherpreneurship requires support from educational institution policies, efficient time management, and the application of professional norms to avoid potential conflicts of interest. This study underscores the crucial importance of maintaining harmony between teaching duties and business activities through institutional arrangements, openness, and careful time management so that entrepreneurship among educators can make a positive contribution to the progress of learning and schools. The results of this study have significant practical implications, as they can be applied as a framework for developing entrepreneurial initiatives for educators in various educational institutions. The goal is to foster an ethos of independence, creativity, and enhanced professional competence among educators, in line with the demands of the contemporary educational landscape.